Desentralisasi dan Hubungan Pemerintah Pusat dan Daerah di Indonesia Problem dan Tantangan - Merlien Irene Matitaputty (SASI, 2012)
In a country like power organization, decentralization is one form of devolution orsharing of authority (power) between the central government and local administrations (localgovernment). Understanding local government may have a double meaning state localgovernment based on the principle of deconcentration, and local self / autonomousgovernment, decentralization leads to Devolution of power. The decentralization policyshould always united with the objectives to democratize governance, strengthening nationalintegration, empowering local communities, respect for diversity, and increased socialwelfare. The four main objectives of decentralization, namely in the fields of economics,politics, administration and culture. In the field of economic decentralization can reduce costsand ensure more effective service (on target). In the political sphere, decentralization developgrassroots democracy, reducing the abuse of power by the center, and will satisfy localpsychologically because given the trust to administer their own affairs. This is wheredecentralization is expected to prevent national disintegration. In the field of administration,decentralization cut rail tape bureaucracy and decision-making more effective. In the field ofsocial and cultural decentralization and develop diversity and appreciate the local culture.